Synthesis and Identification of Glycineamide Complexes of Divalent Metal Ion (Baghdad Science Journal, 2006)
complexes of some divalent metal ions with glycinamide (GlyA) were prepared and identified by R, UV-Visible, atomic absorption, magnetic susceptibility and conductivity measurements.